Facile synthesis of bimetallic CuFe2O4 based ternary hybrid composites for supercapacitor electrodes and optimization of weight ratio of the individuals on the basis of their electrochemical performances - Das T.; Verma B. (My University, 2025)
Electrochemical characterisations like cyclic voltammetry, charge-discharge, electrochemical impedance spectroscopy are performed to find out the best ratio of aniline, acetylene black, and copper ferrite. Polyaniline-acetylene black-CuFe2O4 (PACF1) based two-electrode cell having the weight ratio of 4:1:2 had the highest specific capacitance of 279.48 F/g at 1 mA. It exhibits the highest coulombic efficiency value of 99.5%. PACF1 offers the maximum specific energy and specific power values of 38.81 Wh/kg and 125 W/kg, respectively, at a current of 1 mA. So, PACF1 holds the best weight ratio of aniline, acetylene black, and copper ferrite, i.e. 4:1:2. It exhibits a reasonably low charge transfer resistance of 1.7 Ω. It also has quite good capacitance retention of 85% after 6000 cycles. © 2022 Informa UK Limited, trading as Taylor & Francis Group.